Cytogenotoxicity Test and Biological Evaluation of Curculigo latifolia Extract with Bioindicators Allium cepa L. var. aggregate - Susan Susanti; Nelis Hernahadini; Subagio Joko Suprapto; Haryanto Haryanto (Biology, Medicine, & Natural Product Chemistry, 2025)
Curculigo latifolia plants have secondary metabolites that can suppress cell division. Compounds that suppress cell division can be used as anticancer drug candidates. This research aims to determine the effect of C. latifolia root extract on cell division and genotoxic effects using bioindicator A. cepa L. var. aggregatum. This study was conducted experimentally with a completely randomized design (CRD) using 6 treatment levels and 5 replications. The treatment levels in this study were K (water), K + (H2O2 300 Mm), K - (H2O2 26 hours + water 46 hours) and a combination of treatments at P1, P2, and P3 with H2O2 immersion (26 hours) and continued immersion of C. latifolia root extract concentrations of 400 µg mL-1, 600 µg mL-1 and 800 µg mL-1 (46 hours). The roots of A. cepa from the soaking treatment of C. latifolia extract were used to make preparations using the squash method. The results of the ANOVA test showed that the administration of C. latifolia root extract had a significant effect on the mitotic index and cell abnormalities (P<0.05). P1 had the most effective value in reducing the mitotic index and cell chromosome abnormalities.